Drivers of organizational citizenship behavior of elementary school teachers - Lila Bismala; Syaifuddin Syaifuddin; Rasmulia Sembiring (Institute of Advanced Engineering and Science, 2024)
This study aims to examine the effect of self-efficacy, intrinsic motivation on organizational citizenship behavior (OCB) of elementary school teachers in the post-COVID-19 pandemic mediated by teacher engagement and moderated by job characteristics. A total of 285 valid questionnaires, were analyzed using Structural Equation Modeling with SmartPLS3 software. The results showed that teacher engagement mediates the effects of self-efficacy and intrinsic motivation on organizational citizenship behavior. Job characteristics moderate the effect of intrinsic motivation and self-efficacy on teacher engagement, where moderation in the relationship between intrinsic motivation and teacher engagement is positive, and the moderating role in the relationship between self-efficacy and teacher engagement is negative. This shows that the school must be able to encourage teachers to demonstrate OCB in the school environment, so that teachers are willing to help their students and colleagues deal with learning in the post-pandemic period, in addition to jobs that offer a high degree of autonomy, task variety, task significance, and feedback.